2012
DOI: 10.21161/mjm.33711
|View full text |Cite
|
Sign up to set email alerts
|

Variable responses on early development of shallot (Allium ascalonicum) and mustard (Brassica juncea) plants to Bacillus cereus inoculation

Abstract: Aim: Auxin, a phytohormone secreted by plant growth-promoting rhizobacteria is one of the direct mechanisms vital for plant growth promotion. A laboratory experiment was conducted to observe the effect of IAA-producing and non-IAAproducing diazotroph Bacillus cereus strains on early growth of shallot (Allium ascalonicum) and mustard (Brassica juncea) plants. Methodology and Results: Treatments evaluated were as follows: Control = uninoculated, no inoculation, UPMLH1 = IAA-producing B. cereus UPMLH1, and UPMLH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…BB2, BA37 and SA19 reduced germination percentage, whereas the remaining isolates increased the seed germination. This finding is in line with other researchers who reported various effects of rhizobacteria inoculation on seed germination, either stimulative (Aziz et al 2012, Fatemeh et al 2014, no effect (Pramanik et al 2018), whereas the adverse effect was reported by Arslan and Akkaya (2020). This diverse effect might be due to differences in the production of phytohormone as phytohormone influences seed germination.…”
Section: Discussionsupporting
confidence: 91%
“…BB2, BA37 and SA19 reduced germination percentage, whereas the remaining isolates increased the seed germination. This finding is in line with other researchers who reported various effects of rhizobacteria inoculation on seed germination, either stimulative (Aziz et al 2012, Fatemeh et al 2014, no effect (Pramanik et al 2018), whereas the adverse effect was reported by Arslan and Akkaya (2020). This diverse effect might be due to differences in the production of phytohormone as phytohormone influences seed germination.…”
Section: Discussionsupporting
confidence: 91%
“…Failure of some rhizobacteria to promote plant growth inoculated to non-host plant has been reported by Thokchom et al (2017) who found inoculation of mandarin by host strain enhanced plant growth compared to non-host strain. Moreover, the interaction between soil bacteria and plants can be either beneficial, harmful, or neutral depending on the species of the bacteria and types of plant (Turan et al, 2016) thus demonstrated variable plant responses to inoculation (Aziz et al, 2012). Even though only isolate EN9 indicates some promising effect on plant growth, other isolates demonstrated no deleterious effect upon plant growth (no significance difference at p>0.05 over control).…”
Section: Resultsmentioning
confidence: 99%
“…One hundred grams of soil samples were collected from the previously mentioned regions and kept in polyethylene bags 20x 40 cm. Soil samples were pretreated with CaCO3 at a ratio of 10:1 soil: CaCO3 and kept at an ambient temperature 37ºC to reduce the contamination with molds and yeast, as described by (Aziz, 2022).…”
Section: Treatment Of the Collected Samplesmentioning
confidence: 99%